Relationship quality as a function of luxury car brand image and personality - Loureiro, S. M. C. (2014 Academy of Marketing Science (AMS) World Marketing Congress, 2016)
Luxury means “excess, abundance, extravagant life” (Danziger 2005, p. 17). Adams (2012) expresses luxury as effeminate sensuality and a passion for splendor and pomp. Luxury provides pleasure (Li et al. 2012), comfort, singularity (Lawry et al. 2010) and express desires and emotions (Allérès 2008). Nevertheless, luxury is also connected to subjectivity and its perception and expression varies from society to society (Kemp 1998). Luxury car brands are vehicles that offer features beyond what is basic in an automobile, associated with very high prices, sophisticated design, advanced technology and symbolic elements (Berger 2001; Ulrich 2010). Products, such as cars, and organizations associations can represent the information linked to the node in memory in the consumer’s mind (e.g., Keller 1993; Krishnan 1996; Keller and Lehmann 2006; Qu et al. 2011). Several researchers have demonstrated the positive influence of favourable brand associations on brand image (e.g., Biel 1992; Engel et al. 1993; Keller and Lehmann 2006; Sonnier and Ainslie 2011), regarded as a perceptual phenomenon about a brand as reflected by the brand associations (tangibles and intangibles) held in consumer memory (Keller 1993).